2018
DOI: 10.4103/jpgm.jpgm_598_16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D therapy on urinary albumin excretion, renal functions, and plasma renin among patients with diabetic nephropathy

Abstract: Background:Despite different management strategies, progression of proteinuria occurs in a sizable category of patients with diabetic nephropathy (DN). Increase in serum renin levels induced by the renin–angiotensin system (RAS) may contribute to this. Vitamin D therapy is found to have an inhibitory effect on the RAS. We aimed to study the effects of Vitamin D therapy on renal functions of patients with DN.Methods:This was a double-blind, randomized, placebo-controlled study. Patients with DN (urinary albumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 17 publications
(15 reference statements)
1
33
1
2
Order By: Relevance
“…[ 8 ] In addition, proposed pleiotropic benefits were not observed. Intriguingly, in the current study,[ 9 ] supranormal levels of vitamin D were achieved without adverse effects. Thus, appropriate dosage of vitamin D remains uncertain.…”
supporting
confidence: 49%
“…[ 8 ] In addition, proposed pleiotropic benefits were not observed. Intriguingly, in the current study,[ 9 ] supranormal levels of vitamin D were achieved without adverse effects. Thus, appropriate dosage of vitamin D remains uncertain.…”
supporting
confidence: 49%
“…Proteinuria is the main target to treat in order to prevent and slow down DN and decrease incidence of cardiovascular events 20,21,24 . Vitamin D decreases proteinuria by RAAS inhibition and reduces renal fibrosis by reduction of TGFβ/SMAD pathway [15][16][17] . Vitamin D, apart of renal RASS inhibition, reduces renin expression in heart thereby decreasing arterial blood pressure 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Proteinuria seems to be the most important target to treat in order to prevent cardiovascular events in patients with DN and CKD 13,14,17,20,21 . Paricalcitol and cholecalciferol can decrease proteinuria in patients with CKD or DM [22][23][24][25] .…”
Section: Studies Have Confirmed Low Serum 25-hydroxivitamin D [25(oh)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that vitamin D is a central regulator to control bone and calcium metabolism. Lots of evidence suggested that vitamin D is involved in various renal diseases . Recent research found that a reduced level of vitamin D among CRF patients with and without dialysis, and vitamin D deficiency was associated with vascular calcification, anemia, and cardiovascular mortality in ESRD patients .…”
mentioning
confidence: 99%